High dose statin loading prior to percutaneous coronary intervention decreases cardiovascular events: A meta‐analysis of randomized controlled trials. Issue 1 (21st December 2013) - Benjo, Alexandre M.; El‐Hayek, Georges E.; Messerli, Franz; DiNicolantonio, James J.; Hong, Mun K.; Aziz, Emad F.; Herzog, Eyal; Tamis‐Holland, Jacqueline E.
<x xml:space="preserve">Abstract</x> Objective We performed a meta‐analysis of randomized controlled trials of statin loading prior to percutaneous coronary intervention (PCI). Background Statin loading prior to PCI has been shown to decrease peri‐procedural myocardial infarction (pMI) but less is known regarding the clinical benefit of pre‐procedural statin loading. Methods We searched for trials of statin naïve patients presenting with stable angina or NSTE‐ACS and treated with statins prior to PCI. We evaluated the incidence of pMI and major cardiac events including spontaneous myocardial infarction, death, and target vessel revascularization. Results Out of 1, 210 articles, 14 randomized controlled trials were included in this meta‐analysis. Among 3, 146 patients, 1, 591 patients were randomized to a loading dose of statin before PCI and 1, 555 patients were given statin therapy initiated only after the PCI. Statin loading prior to PCI was associated with a 56% relative reduction in pMI (OR: 0.44, 95% CI: 0.35–0.56; P < 0.00001). There was a 41% reduction in clinical events in follow‐up in the group of patients treated with statin loading prior to PCI (OR: 0.59, 95% CI: 0.38–0.92, P = 0.02). When stratified according to the clinical presentation, the results were only significant for those patients with NSTE‐ACS (OR: 0.18, 95% CI: 0.07–0.47; P = 0.0005) and was not noted in the group of patients who underwent PCI for stable angina (OR: 0.92, 95% CI: 0.53–1.61; P = 0.78). Conclusions High dose statin therapy given prior to PCI in patients with NSTE‐ACS is associated with a reduction in pMI and short‐term clinical events. © 2013 Wiley Periodicals, Inc.